1989
DOI: 10.1002/aja.1001840104
|View full text |Cite
|
Sign up to set email alerts
|

Tracheobronchial epithelium in the adult rhesus monkey: A quantitative histochemical and ultrastructural study

Abstract: Previous studies of the intrapulmonary conducting airways of sheep and rabbit have demonstrated marked diversity in the epithelial populations lining them. Because studies of trachea and centriacinar regions of macaque monkeys suggested that primates may be even more diverse, the present study was designed to characterize the epithelial population throughout the airway tree of one primate species, the rhesus monkey. Trachea and intrapulmonary airways of the right cranial and middle lobes of glutaraldehyde/para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 20 publications
1
52
0
Order By: Relevance
“…Other investigators have reported colocalization of CCSP and mucins (8,30) in the human lung similar to what we report here in the monkey. These findings suggest CCSP expression in rhesus monkey airway epithelium is outside the classic lineage defined by TEM in distal airways by Plopper et al (23,24). When comparison is made of airways throughout the tracheobronchial tree that are identified by their branching history, immunoreactive CCSP was detected throughout the intrapulmonary airway tree from the lobar bronchus to the respiratory bronchioles.…”
Section: Discussionmentioning
confidence: 69%
“…Other investigators have reported colocalization of CCSP and mucins (8,30) in the human lung similar to what we report here in the monkey. These findings suggest CCSP expression in rhesus monkey airway epithelium is outside the classic lineage defined by TEM in distal airways by Plopper et al (23,24). When comparison is made of airways throughout the tracheobronchial tree that are identified by their branching history, immunoreactive CCSP was detected throughout the intrapulmonary airway tree from the lobar bronchus to the respiratory bronchioles.…”
Section: Discussionmentioning
confidence: 69%
“…Further subsampling may be necessary to reduce small airway samples to a practicable number. Alternatively, microdissection can be used to define and localize samples to airway generations (34,159).…”
Section: Conducting Airwaysmentioning
confidence: 99%
“…Rhesus monkeys were used because they have similar lung cellular morphology, airway architecture, and immunology and undergo a similar extensive period of postnatal development compared with humans (35)(36)(37)(38)(39). In addition to possessing all of the components of the intrapulmonary conducting airways that are altered in humans with asthma, rhesus monkeys display a similar progression of asthma pathophysiology and symptoms (11,40).…”
Section: Clinical Relevancementioning
confidence: 99%